EFEKTIVITAS YOUTUBE SEBAGAI MEDIA BELAJAR MASYARAKAT (DUSUN BENDAKULON RT 04/16 PADANGJAYA, MAJENANG) - Solehudin, Much; M.Kom, Ratih (Jurnal Teknologi dan Bisnis, 2020)
This study aims to determine the level of effectiveness of YouTube as a learning medium in society. Themethod used in this research process is descriptive qualitative method. While data collection techniques,the authors explore the data according to the discussion by looking at various journals, articles andinformation from relevant YouTube users in the problems observed. The results of this study indicate thatthe level of use of YouTube in the community can be said to be high, because apart from being a learningmedium, they open YouTube to be used as a medium of entertainment. People who use YouTube as alearning medium are people who have their own interests or when in an emergency they want to find outthe solution to the problems they face, for example opening a video tutorial on dealing with cellphones,washing machines, televisions, refrigerators or other damaged household items. By watching the video,finally the community can put it into practice. In addition, there are also many other ways such as how tocare for ornamental plants, from planting to growing big. All can be practiced via Youtube media. Peoplefeel they can add to their knowledge without having to spend a lot of money, meaning they consider itmore efficient because one click directly displays audio and visuals that can be imitated or applied. Mostpeople feel that YouTube has a positive impact on those in need.